Answer:
(x - 6)(x - 6)
Step-by-step explanation:
The given quadratic equation is
.
A quadratic equation can be factored in the form
where
and
will form the roots of the equation.
Here the roots are:
.
The factored form would simply be:
.
Answer:
x= 1/4 .....................
y=-1
The answer is the first option, you multiply 14^2 by 9
Answer: x + 12 = 3x + -22
12 + x = 3x + -22
Reorder the terms:
12 + x = -22 + 3x
Solving
12 + x = -22 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
12 + x + -3x = -22 + 3x + -3x
Combine like terms: x + -3x = -2x
12 + -2x = -22 + 3x + -3x
Combine like terms: 3x + -3x = 0
12 + -2x = -22 + 0
12 + -2x = -22
Add '-12' to each side of the equation.
12 + -12 + -2x = -22 + -12
Combine like terms: 12 + -12 = 0
0 + -2x = -22 + -12
-2x = -22 + -12
Combine like terms: -22 + -12 = -34
-2x = -34
Divide each side by '-2'.
x = 17
Simplifying
x = 17
Answer:
[See Below]
Step-by-step explanation:
__________________________
✦ Solve for
:
__________________________
✦ Solve Parenthesis first:
__________________________
✦ Add all the values together:
__________________________
So Mikayla wrote the decimal correctly.
__________________________
~<em>Hope this helps Mate. If you need anything feel free to message me.</em>
☺